The great American biotic interchange revisited (2010)
The “Great American Biotic Interchange” (GABI) is regarded as a defining event in the biogeography of the Americas. It is hypothesized to have occurred when the Isthmus of Panama closed ca three million years ago (Ma), ending the isolation of South America and permitting the mixing of its biota with that of North America. This view of the GABI is based largely upon the animal fossil record, but recent molecular biogeographic studies of plants that show repeated instances of long?distance dispersal over major oceanic barriers suggest that perhaps the land bridge provided by the isthmus may have been less necessary for plant migration. Here we show that plants have significantly earlier divergence time estimates than animals for historical migration events across the Isthmus of Panama region. This difference in timing indicates that plants had a greater propensity for dispersal over the isthmus before its closure compared with animals. The GABI was therefore asynchronous for plants and animals, which has fundamental implications for the historical assembly of tropical biomes in the most species?rich forests on the planet.